1993
DOI: 10.1002/micr.1920140314
|View full text |Cite
|
Sign up to set email alerts
|

En bloc kidney and whole pancreaticoduodenal transplantation with bladder drainage in the rat: Microsurgical technique and outcome

Abstract: A microsurgical technique for en bloc kidney and whole pancreaticoduodenal transplantation with bladder drainage employing triple vascular anastomoses without the need for a vascular cuff is described. Nineteen combined isografts were performed using this technique in inbred male Lewis (RT1:I) rats with streptozotocin-induced diabetes. Six recipients died within 1 month from early complications (two from uremia, two from pancreatitis, one from bleeding, one from peritonitis); the other 13 survived more than 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, some studies showed that PTx with enteric diversion of the exocrine graft secretion part is more prone to intestinal bleeding and ileus and increases the chance of bacterial contamination because of the bowel opening [19]. The urinary diversion of the exocrine part of the graft has some benefits over the enteric one such as avoiding opening of the recipient bowel and minimization of bacterial contamination, direct monitoring of the pancreas for rejection, as well as lesser morbidity of anastomotic leaks from urinary anastomosis [10]. However, dehydration and acidosis, recurrent urinary tract infections, reflux graft pancreatitis, and hematuria with the occasional need for conversion to the enteric drainage are some disadvantages of urinary exocrine drainage [11].…”
Section: Comments On Surgical Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, some studies showed that PTx with enteric diversion of the exocrine graft secretion part is more prone to intestinal bleeding and ileus and increases the chance of bacterial contamination because of the bowel opening [19]. The urinary diversion of the exocrine part of the graft has some benefits over the enteric one such as avoiding opening of the recipient bowel and minimization of bacterial contamination, direct monitoring of the pancreas for rejection, as well as lesser morbidity of anastomotic leaks from urinary anastomosis [10]. However, dehydration and acidosis, recurrent urinary tract infections, reflux graft pancreatitis, and hematuria with the occasional need for conversion to the enteric drainage are some disadvantages of urinary exocrine drainage [11].…”
Section: Comments On Surgical Techniquesmentioning
confidence: 97%
“…The current preferred method for rearterialization is the microsuture technique, which provides an anastomosis more similar to the physiological setting. Although the use of cuff technique has simplified the arterial anastomosis and decreased complications associated with the microsuture technique by means of reduction in warm ischemia time and thrombosis [9], its high rate of technical failure [10] reduces its acceptance among surgeons (Table 1).…”
Section: Comments On Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…PDKTs in rats were first described by Nakai et al [2]in 1993. It lasted 6 years until Lee et al [1]repeated the model.…”
Section: Discussionmentioning
confidence: 99%
“…Rats have been widely used in transplantation models because of their low cost and the opportunity to manipulate immune responses by selecting inbred and outbred strain combinations. It is a difficult problem to build a small-animal model with combined pancreaticoduodenal-kidney transplantation (PDKT) because of complex surgical technique [1, 2]. In our study, we performed two ‘cuff’ anastomoses [3]to converge donor portal vein and left kidney vein into the inferior vena cava (IVC) together and to overcome donor venous outflow in two directions.…”
Section: Introductionmentioning
confidence: 99%